PSVIII-16 Interferon-TAU in the pathogenesis and prevention of intrauterine growth restriction and embryonic death in dairy cows. (30th November 2020) - Shabunin, Sergey; Mikhalev, Vitaliy; Nezhdanov, Anatoly; Safonov, Vladimir; Parshin, Pavel; Anipchenko, Polina
Abstract: The aim of the research was to assess the state of the hormonal and cytokine blood profiles of Holstein dairy cows during the early period of gestation with physiological formation of the embryo, its intrauterine growth restriction and death, clarify the pathogenetic mechanisms of these embryopathologies development and identify the efficacy of their prevention using recombinant bovine INFT. The dynamics of serum concentration of P4, cortisol (F) and cytokines: INFT, interleukin IL-2, tumor necrosis factor (TNFα), interferon-γ (INF-γ) at the physiological formation of the embryo (n = 9), its growth restriction (n = 9) and death (n = 8) were studied. The blood samples were obtained on the day of artificial insemination, during early blastogenesis (days 8–9), implantation of the embryo (days 15–16), the formation of primary genital organs (days 32–33), and at the end of the embryonic period of development (days 60–65). In cows with intrauterine growth restriction and embryonic death, serum concentration of P4, compared with the cows demonstrating their physiological formation, was lower by 14.0–30.1%, F - by 11.2–35.5%, INFT - by 21.0–37.7% when the content of IL-2 was exceeded by 46.5–310.5%, TNFα - by 11.7–36.2%, INF-γ - by 58.0–296.0%. A statistically significant positive correlative relationship between the content of INFT, P4, F and a negative one with the indices of the concentration of proinflammatory cytokines was found. Violation of the hormonal-cytokine balance in the organisms of fertilized animals is a universal pathogenetic mechanism for the development of early embryopathies. Injections of recombinant bovine INFT to inseminated cows during the pre- and implantation periods increased the level of progesterone production and reduced the synthesis of proinflammatory cytokines. The efficacy of insemination of cows increased by 1.96 times, the manifestation of fetal/embryonic intrauterine growth restriction syndrome decreased by 2.35 times in comparison with the control animals.